Assessment of service traffic dependences in Ad-hoc networks - Teleshko, I. (Problems of Informatization and Management, 2025)
The article devoted to the problem of excessive service traffic in wireless ad-hoc networks, which arises due to the lack of a fixed infrastructure, dynamic topology, and limited node resources. Service traffic is interpreted from an information-theoretic point of view as a mechanism for reducing uncertainty about the network state. A mathematical model is proposed that relates the intensity of service traffic to the number and density of nodes, the level of interference, and the signal-to-noise ratio in communication channels. It is shown that for a fixed deployment area, an increase in node density leads to a superlinear, close to quadratic, increase in network management overhead. Special attention is paid to the possibilities of reducing the effective node density due to algorithmic routing mechanisms, in particular, approaches such as ND-AODV, which allow significantly reducing the volume of service traffic in dense networks. The results obtained can be used to assess the scalability of ad-hoc networks and develop more effective management protocols.